The Effectiveness of Task-Based Approach in Enhancing the Writing Skill of E.F.L learners - Ammour, Amina (My University, 2018)
The present study aims to evaluate the influence of task –based Approach strategies in enhancing writing skill of the fourth year pupils at middle school. This study illustrates that Task-Based Language Teaching (TBLT) can improve writing competence. In this research two different research tools were used: teachers and learners ‘questionnaires besides classroom observation in both of “Ammour Mohamed” and “Boulaars Mekhelouf” schools in Kheir Eddine Mostaganem. Concerning learners analysis there are three methods of data collection: including observation, questionnaire and writing paragraph in order to improve their writing abilities. Through writing, we communicate our ideas to readers. Therefore, writing skill is important for pupils because through writing they can write and reflect their level in exams. Consequently, the results affirme that the use of TBLT in teaching is a very useful and effective approach in enhancing writing skills to the most of the fourth year pupils depending on their ability to learn and acquiring the appropriate ways to produce a meaningful paragraph.
Case of Study Fourth Year Middle School Pupils,in ”Ammour Mohamed “and “Boulaas Mekhlouf”schools in Kheir Eddinne Mostaganem
Keywords: TBLT: Task-Based Language Teaching; Evaluation; Approach strategies